FABRICATION OF STEAM TURBINE SIMULATOR BASED ON FUZZY LOGIC - Syukri Yusuf Nasution (Pusbindiklat - LIPI, 2011)
A steam turbine simulator has built successfully. This simulator has 2 types, hardware and software simulator. For the hardware simulator, the pressure input can be simulated until 8 bar. While for the software simulator has 2 speciﬁ cations those are off-line mode and on-line mode. For off-line mode, this software given numbers as input, and then the numbers simulated according to the formulas. For on-line mode, interface method used to read and control the system hardware directly. The result of on-line mode displayed in real-time graphic. All systems using fuzzy logic as artiﬁ cial intelligent.